2014
DOI: 10.4067/s0717-95022014000400002
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Hepatic Artery Arising from Celiac Trunk: An Incidence in a Thai Cadaver

Abstract: SUMMARY: An exhaustive knowledge of the liver vascular patterns as well as possible anatomical variations is significant in the planning and performance of all liver surgical procedures in order for the vascularity not to be disturbed or not causing necrosis of the liver parenchyma postoperatively. The celiac trunk usually provides three branches; left gastric, splenic and common hepatic arteries. The left and right hepatic arteries generally derive from proper hepatic artery which is a branch of common hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…15 Similar to few authors there was not a single case of type III pattern in this study. [16][17][18] In contrast, many studies revealed type III variation and they recorded this configuration in15.16% and 16% respectively. 11,12 A study quoted the occurrence of this variant in majority (25%) of the studied cases.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similar to few authors there was not a single case of type III pattern in this study. [16][17][18] In contrast, many studies revealed type III variation and they recorded this configuration in15.16% and 16% respectively. 11,12 A study quoted the occurrence of this variant in majority (25%) of the studied cases.…”
Section: Discussionmentioning
confidence: 99%
“…Neglecting the variant gastric artery can cause damage to the gastric artery, leading to gastric ischemia. An anomalous branching pattern is often due to the original embryonic life, as explained by Chanasong et al (2014). During embryonic development, the stomach and liver are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the right hepatic artery from the superior mesenteric artery is very rare but forms an important clinical relation with the surrounding structures such as the head of the pancreas, first part of duodenum and portal vein, making it vulnerable during the surgeries. According to the study done by Chanasong et al, an additional accessory hepatic artery originated from the left aspect of the celiac trunk entering the porta hepatis of the liver in the Thai patient [9]. The cystic artery plays an important role in supplying the cystic duct and the gall bladder.…”
Section: Case Reportmentioning
confidence: 99%